Postinflammatory sarcoma in cats - Jelínek, Frantisek (Experimental and toxicologic pathology, 2003)
Histological examination of 38 nodular formations extirpated from the site of vaccine administration to cats disclosed 25 cases of sarcoma and 13 of granuloma. Average age of the cats bearing sarcoma was 8.75 years whereas granuloma occurred at average age of 1.9 year. This age-relationship of the lesions, as well as their similar morphologic features indicated a progression of chronic inflammatory changes to tumors. Similar tumors were diagnosed in one cat with "posttraumatic ocular sarcoma" and in the uterus of female-cat with long-standing pyometra. These two cats were 15 and 8 years old, respectively. Experimental study of local reaction 21 days after administration of commercial, lipid-adjuvanted vaccine revealed in young cats (age 9 months) a reaction to immunogen, whereas in old animals (age 10 to 15 years) there was a reaction to foreign material. The data suggest that chronic inflammation and age-related immunodeficiency are instrumental in pathogenesis of the vaccine-associated sarcoma.
Keywords: Alkaline Phosphatase; Soft Tissue Neoplasms; vakcinace; kočky; alkalická fosfatasa; sarkom; Vaccination; Immunoenzyme Techniques; Female; Inflammation; zvířata; Cat Diseases; nemoci koček; zánět; kyselá fosfatasa; nádory měkkých tkání; imunoenzymatické techniky; ženské pohlaví; Sarcoma; Male; imunokompromitovaný pacient; Acid Phosphatase; Animals; Cats; mužské pohlaví; Immunocompromised Host; karboxylesterasa; Carboxylesterase